ANALISIS PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR INDUSTRI ( KERAMIK, PORSELEN DAN KACA ) - -, Lusia Mandasari (EKONOMIA, 2018)
This Formula research internal issue" Is ratio of net margin profit, asset on return, equity on return, and earning per share have an effect on signifikan to share price which enlist at BEI sector sub of industry (ceramic, Porselen, and glass) in the year 2011-2015?This research aim to to know influence of ratio of net margin profit, asset on return, equity on return, and earning per share have an effect on significant to share price which enlist at BEI industrial sector sub (ceramic, Porselen, and glass) in the year 2011-2015.Research method by using obtained data of Effect Exchange Indonesia. Population is all company of ceramic industrial sector sub, glass and porselen which enlist in BEI 2011-2015. Research Sampel counted 6 company Analyzer the used doubled linear regresi which where beforehand have to test classic assumption.Pursuant to result of solution and research hence Ratio of net margin profit (NPM) have an effect on not signifikan to share price which enlist in BEI industrial sector sub (ceramic, Porselen, and glass). ratio of Return asset on (ROA) not have an effect on signifikan to share price which enlist in BEI industrial sector sub (ceramic, Porselen, and glass). ratio of Return equity on (ROE) not have an effect on signifikan to share price which enlist in BEI industrial sector sub (ceramic, Porselen, and glass). ratio of Earning per share (EPS) have an effect on signifikan to share price which enlist in BEI industrial sector sub (ceramic, Porselen, and glass). Profitability ratio (NPM, ROA, ROE, and EPS) having an effect on significan to share price which enlist in BEI industrial sector sub (ceramic, Porselen, and glass)